2017
DOI: 10.1002/ange.201709026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Phlorin from a Meso‐Fused Anthriporphyrin by a Diels–Alder Strategy

Abstract: An anthracene-containing meso-fused carbaporphyrin, whichh as extended p-conjugation pathwaysa sc ompared to the corresponding naphthalene-containing carbaporphyrin, has been synthesized.T he weak global aromaticity of the anthriporphyrin also allowed its use as the diene for aD iels-Alder reaction with dimethyl acetylenedicarboxylate (DMAD). The resulting phlorin contains an interesting bicyclic structure.M oreover,t ot he best of our knowledge, this phlorin is the first Diels-Alder adduct of ad iene forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…1) possess quite different and novel features. 14 We and others have reported the synthesis of various PAH-embedded porphyrinoids such as biphenyl, 15 bipyridyl, 16 naphthalene, 17 anthracene, 18 phenanthrene, 19 phenanthroline, 20 fluorene, 21 dibenzofuran/thiophene, 22 phenothiazine 23 and pyrene 24 incorporated porphyrinoids. Some of these PAH-embedded porphyrinoids showed very unusual and interesting structures and spectral and coordination properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) possess quite different and novel features. 14 We and others have reported the synthesis of various PAH-embedded porphyrinoids such as biphenyl, 15 bipyridyl, 16 naphthalene, 17 anthracene, 18 phenanthrene, 19 phenanthroline, 20 fluorene, 21 dibenzofuran/thiophene, 22 phenothiazine 23 and pyrene 24 incorporated porphyrinoids. Some of these PAH-embedded porphyrinoids showed very unusual and interesting structures and spectral and coordination properties.…”
Section: Introductionmentioning
confidence: 99%
“…15 Similarly, Cho and co-workers reported anthracene embedded porphyrin and demonstrated that the anthracene moiety of the porphyrinoid undergoes a Diels–Alder addition reaction to form the stable Diels–Alder product of anthracene embedded porphyrinoids. 18 We reported the synthesis of antiaromatic meso -fused heterobenziporphyrins using fluorene as a fused polyaromatic hydrocarbon motif embedded in the macrocycle and used them for the synthesis of a cationic organo palladium( ii ) complex. 21 In continuation of our efforts towards developing new PAH embedded porphyrinoids, herein we report the synthesis and studies of phenothiazine embedded porphyrins called here phenothiazinophyrins 2–4 which resulted from the replacement of one of the pyrrole rings of porphyrin with a phenothiazine moiety (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] In recent times, polycyclic aromatic hydrocarbon/heterocycle (PAH) embedded porphyrinoids have received significant attention due to their unique properties exhibiting the features of both PAH and porphyrinoids. Different polycyclic aromatic hydrocarbons/ heterocycles such as naphthalene, [8] dibenzofuran/ thiophene, [9,10] anthracene, [11] pyrene, [12] fluorene, [13,14] bipyridine, [15] phenanthroline, [16] phenothiazine, [17a-c] and so on have been incorporated into the framework of porphyrinoid in place of one or two pyrrole/heterocycle rings and explored their electronic and structural properties. Among different polycyclic aromatic heterocycles, phenothiazine (PTZ) is very important as this heterocycle is widely used in the synthesis of various organic dyes [18] such as methylene blue, [19] methylene green, [20] thionine [21] and also in certain pharmaceutical drugs such as chlorpromazine [22] and so on.…”
Section: Introductionmentioning
confidence: 99%